2018
DOI: 10.3389/fchem.2018.00530
|View full text |Cite
|
Sign up to set email alerts
|

ctDNA Detection Based on DNA Clutch Probes and Strand Exchange Mechanism

Abstract: Circulating tumor DNA (ctDNA), originating directly from the tumor or circulating tumor cells, may reflect the entire tumor genom and has gained considerable attention for its potential clinical diagnosis and prognosis throughout the treatment regimen. However, the reliable and robust ctDNA detection remains a key challenge. Here, this work designs a pair of DNA clutch separation probes and an ideal discrimination probes based on toehold-mediated strand displacement reaction (TSDR) to specifically recognize ct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For the completeness of the discussion on ctDNA biosensors, the optical sensing methods of ctDNA are briefly presented as follows. Chang et al [ 58 ] proposed a fluorescence polarization method to detect ctDNA based on DNA dissociation probe and chain exchange mechanism and used toehold-mediated strand displacement reaction (TSDR) to identify the specific binding of probes to target mutated DNA to generate fluorescence for qualitative analysis. Jin et al [ 59 ] designed and synthesized a water-soluble cationic fluorescent probe and found that fluorescence intensity was linearly proportional to ctDNA concentration at a certain concentration.…”
Section: Other Ctdna Biosensing Methodsmentioning
confidence: 99%
“…For the completeness of the discussion on ctDNA biosensors, the optical sensing methods of ctDNA are briefly presented as follows. Chang et al [ 58 ] proposed a fluorescence polarization method to detect ctDNA based on DNA dissociation probe and chain exchange mechanism and used toehold-mediated strand displacement reaction (TSDR) to identify the specific binding of probes to target mutated DNA to generate fluorescence for qualitative analysis. Jin et al [ 59 ] designed and synthesized a water-soluble cationic fluorescent probe and found that fluorescence intensity was linearly proportional to ctDNA concentration at a certain concentration.…”
Section: Other Ctdna Biosensing Methodsmentioning
confidence: 99%
“…Chang et all. [51] proposed a fluorescence polarization method to detect ctDNA based on DNA dissociation probe and chain exchange mechanism, and used toehold-mediated strand displacement reaction (TSDR) to identify the specific binding of probes to target mutated DNA to generate fluorescence for qualitative analysis. Jin J et all.…”
Section: Other Ctdna Biosensing Methodsmentioning
confidence: 99%
“…Level Reference Electrochemical method based on DNA probe fM [34], [38], [39], [41], [42] Electrochemical method based on antigen antibody fM [51], [52] Fluorescence method pM [57],[58] Amplified colorimetric method pM [59]…”
Section: Methodsmentioning
confidence: 99%
“…In a recent approach, Chang et al developed a magnetic nanoparticle-based separation technique for BRAF ctDNA purification, and achieved a detection limit of 0.85 × 10 −9 m in serum samples. [39] In this method, magnetic nanoparticles functionalized with clutch separation probes were designed to bind to complementary strands and prevent reassociation of denatured ssDNA sequences. After removal of complementary strands by magnetic separation, toehold-mediated strand displacement reaction was further used to specifically recognize BRAF target mutant sequences for fluorescence detection.…”
Section: Protein Preparationmentioning
confidence: 99%